The Hostage [Backstage] - https://finding-aids.library.gatech.edu/agents/corporate_entities/112; Georgia Institute of Technology. DramaTech Theatre (1994)
CAST: George Bowling (Monsewer), Amanda Canup (Teresa), Gayle Casey (Bernadette), Miguel Forjan (Rio Rita), Mira Hirsch (Miss Gilchrist), Lorna Howley (Meg Dillon), Karla Jennings (Siobhan), Lori Kessler (Street Vendor), David Klein (IRA Man), Christopher Kolz (Feargus O'Connor), John Liles (IRA Officer), Charles Loflin (The American Exchange Student), Michael Lott (Princess Grace), Donald 'Doc' Lumpkins (Russian Sailor), Andrew Malkus (IRA Man), Daniel May (Leslie), Lorraine (Allen) Rose (Whore), Jason Smucker (Kevin), John Stephens (Pat), Suzanne Tilleman (Colette), Anthony A 'Tony' Vila (Mulleady). CREW: Frank Miller (Director), C Edward 'Eddie' Maise (Assistant Director), John Stephens (Artistic Director), Jimmy Rose (Music Director), Laurie Scally (Stage Manager), Brandon Smith (Assistant Stage Manager), Heather (Stehman) Lott (Assistant Stage Manager), Zvi William 'Wil' Bakal (Assistant Stage Manager), David Gibbs (Set Designer), Bret Skelton (Master Carpenter), Robert Casey (Lighting Designer), Brian 'Egon' Smith (Master Electrician), Scott Sargent (Light Operator), Brian 'Egon' Smith (Sound Designer), David Darwin Clark (Sound Operator), John Miniat (Properties Designer), Chelsey Ford (Properties Designer), Kristi Andur (Costume Designer), Kris Cole (Makeup), Vicky A Pickens (Festival Publicity Director), Karen Exline (Assistant Publicity), Christa Segers (Assistant Publicity), Jerrilyn Levetan (Program Designer), Walker Scott (Program Designer), Mike 'Piv' Pivovar (House Manager), Mike 'Piv' Pivovar (Box Office Manager), Steven Sams (Composer), David 'Dave' Cater (Musician), Steven Sams (Musician), Jim Peliksza (Musician), Andy Fleming (Musician), Jimmy Rose (Musician).